THE INFLUENCE OF LEGAL REGULATION ON HUMAN RESOURCE MANAGEMENT PRACTICES - Erwin Erwin; Abdul Rauf; M. Yunus Idy (Adisam Publisher, 2025)
The influence of legal regulations on human resource management practices includes how applicable regulations and laws affect the way an organisation manages its personnel, including the processes of hiring, training, appraising and developing employees. These regulations aim to ensure that fair labour practices are implemented to protect workers' rights and create a safe and inclusive work environment, while forcing companies to continuously improve their operational standards to meet or exceed legal requirements set by government authorities. The research method used was a literature review. The results show that legal regulations have substantial influence in setting norms for recruitment, training, pay and equality in the workplace. Regulation enhances organisations' adherence to high standards in terms of employee rights and working conditions. Furthermore, it was found that while there is a view that regulation can be restrictive, it actually often encourages organisations to innovate in order to improve efficiency and competitiveness.